PERLINDUNGAN HUKUM TERHADAP KONSUMEN DALAM PENGGUNAAN KANTONG PLASTIK HITAM PADA KEMASAN MAKANAN DI PASAR TRADISIONAL SENAPELAN KECAMATAN SENAPELAN KOTA PEKANBARU - Saleha Saleha; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Law Number 8 of 1999 concerning Consumer Protection, is intended to be a strong legalbasis for consumers and business actors for their rights and obligations, as well as a strong legalbasis for government and non-governmental consumer protection institutions to make efforts toempower consumers through coaching and consumer education. The rapid advancements intechnology now bring a variety of new products that can meet consumer needs. The use of goodtechnology, on the one hand, enables producers to be able to make products of various types,shapes, uses and qualities so that the fulfillment of consumer integrity can be fulfilled more widely,but on the other hand the use of technology enables the production of products that are not inaccordance with the security and safety requirements of users. to consumers. Food safety is one ofthe important factors that must be considered in daily consumption. Packaging in food also has thefunction of health, preservation, ease, uniformity, promotion and information. But not all foodpackages are safe for the food they pack. Therefore, the purpose of this paper is: First, the causesof the circulation of black plastic bags at the Senapelan Traditional Market, Senapelan District,Pekanbaru City; Second, efforts made by the government in overcoming the use of black plasticbags at the Senapelan Traditional Market, Senapelan District, Pekanbaru City.This type of research can be classified in the type of sociological juridical research, becausein this study the author immediately approached by looking in terms of legislation and the realitythat occurred in the field, according to the formulation of the problem expressed by the author. Thisresearch was conducted at the Senapelan Traditional Market, Senapelan District, Pekanbaru City,a plastic bag trader and BBPOM in Pekanbaru City.The conclusions that can be obtained from the results of the study are: First, the causes ofthe circulation of black plastic bags in the Senapelan Traditional Market, Senapelan District,Pekanbaru City, due to the absence of strict sanctions from the government, lack of consumerknowledge and lack of knowledge of business actors. Second, the efforts carried out by Pekanbaru'sBBPOM in the use of plastics are: First, conducting food safety counseling, disseminatinginformation through mass media and electronics, disseminating information through exhibitions;Second, the efforts made by businesses in the use of black plastic bags are: striving for goods and /or services circulating in the community to be products that are worthy of circulation; Third, effortsmade by consumers, namely: thorough before using a product, make a complaint if foundsomething wrong, pay attention to the quality of goods, know the rights and obligations ofconsumers.Keywords: Legal Protection – Consumer – Plastic Bag